Enemies among us : the relocation, internment, and repatriation of German, Italian, and Japanese Americans during the Second World War - Schmitz, John E. (University of Nebraska Press, 2021)
John E. Schmitz examines the causes, conditions, and consequences of America's selective relocation and internment of German, Italian, and Japanese Americans during World War II.